Implementasi Teori Antrian Single Chanel Model (M/M/1) Menggunakan Microsoft Excel Dalam Pengujian Kelayakan Kendaraan Bermotor Pada Dinas Perhubungan Kota Medan - Siti Khadijah Laoly; Wilia Usna; Nurhalimah Ritonga; Hendra Cipta (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Vehicle testing in this research was carried out in the Practical Work Lecture program at the North Sumatra State Islamic University, MedanOne type of service provided is motor vehicle testing. Motor vehicle testing is very important to carry out for the safety of the driving public. When testing motorized vehicles, not only one vehicle will be tested, but many vehicles will be tested every day. The testing carried out will of course take quite a long time. Therefore, this research will use a queuing theory system, where this queue will be formed and help in managing and optimizing performance in motor vehicle testing. In this research, we will lokk at the service time and waiting time required for motor vehicle testing. The method used in this research is data taken in 2022. The data was processed using Microsoft Ecxel with service time results of 15,8 and waiting time of 57,05.